SOCIAL MEDIA STRATEGY: UTILIZING INSTAGRAM TO SHAPE LOCAL, WISDOM-BASED SALES MESSAGES IN A COFFEE SHOP - Purnamasari, Oktaviana; Rahim, Norhayati Rafida Abdul; Badri, Muhammad; KN, Jamiati; Hasna, Sofia (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2023)
Micro, Small and Medium Enterprises (MSMEs) possess an extraordinary potential to cultivate. One of the MSMEs that are commonly found is coffee shops. Kedai Kopi 1956 is one from many coffee shops that are currently flourishing, which is located in Kampung Batik Laweyan, Solo. Based on the local wisdom of Kampung Batik Laweyan, Solo, Kedai Kopi 1956 builds sales messages through social media strategies on Instagram. The aim of this research was to identify Kedai Kopi 1956's Instagram social media strategy in building sales messages and utilizing local wisdom as its core. The theory used in analyzing this research was the social media strategy theory by Quesenberry. This research resorts to a descriptive qualitative approach. Data collection techniques includes interview with key informant and observations on the Instagram account @1956.mor. Results revealed that the Instagram social media strategy for building sales messages based on local wisdom was carried out by Kedai Kopi 1956 using three different approaches as expressed by Quesenberry: 1) Determining objectives, target audience and social analysis; 2) Determining the message: creating a big idea, namely Kedai Kopi 1956 always promotes simplicity, attempting to be humble and provides deeper meaning to others, which are  then conveyed in the form of major ideas into inspirational stories; and 3) Integrating Social Media with Marketing in the form of selling merchandise, Advertising by uploading inspirational stories to attract visitors and Public Relations by supporting current hot issues such as independence and peace in Palestine as well as collaborating with third parties, the Surakarta City Tourism and Culture Office to create video profiles.